PENGARUH PEMBERIAN TEPUNG MAGGOT BLACK SOLDIER FLY (Hermetia Illucens) DALAM RANSUM TERHADAP BOBOT POTONG, BOBOT KARKAS, PERSENTASE KARKAS AYAM KAMPUNG JOPER(Gallus-gallus Domesticus) UMUR 60 HARI - Pardosi, Untung (Jurnal Peternakan (Jurnal of Animal Science), 2023)
This study aims to determine the addition of black soldier fly (Hermetia illucens) maggot flour in the ration on slaughter weight, carcass weight, carcass percentage of Joper kampung chicken aged 60 days. This research was conducted at the Experimental Field of the Faculty of Animal Husbandry, University of HKBP Nommensen in Simalingkar A Village, Pancur Batu District, Deli Serdang Regency. This research was conducted for 60 days. This study used 100 Joper kampung chickens. The research method used was an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 5 replications namely P0 (0% BSF maggot flour in rations), P1 (5% BSF maggot flour in rations), P2 (10% BSF maggot flour BSF in rations) and P3 (15% BSF maggot flour in rations). The data obtained in this study will then be analyzed for variance (ANOVA) and then followed by the Honest Significant difference test (BNJ). The conclusion obtained from the results of this study was that the administration of BSF maggot flour in the Joper kampung chicken ration had a very significant effect (P<0.01) on slaughter weight while the chicken carcass weight, the percentage of Joper kampung carcass showed no significant difference (P>0.05 ). Provision of BSF maggot flour in Joper kampung chicken rations is recommended up to a level of 5%.